The idea of a system increasing flight safety - Tomasz Rogalski (Aviation, 2010)
This paper presents a conception of an airborne control system that can increase the safety of a general aviation aircraft. Sample threats appear on board the general aviation airplane discussed in the paper. The system monitors some events and flight parameters in the cockpit and can take some actions protecting the plane against threats if recognised as necessary. The paper presents sample actions fly‐by‐wire control systems can take to protect a plane against some threats on board. The system can modify a pilot's controls to correct flight and if it is not enough the system can disengage the pilot to autonomously fly the plane to the nearest safe airport